1982
DOI: 10.1161/01.hyp.4.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lesions of the anteroventral third ventricle (AV3V) on the development of hypertension in spontaneously hypertensive rats.

Abstract: SUMMARY Lesions of the anteroventral third ventricle (AV3V), an angiotensin and osmosensitive region of the anterior hypothalamus, prevent or abort hypertension in a number of rat models. To determine if A V3V lesions alter hypertension in spontaneously hypertensive rats (SHR), lesions and control sham lesions were made in young SHR at 28 days of age. AV3V lesions had no effect on the development of hypertension in SHR. However, lesioned rats demonstrated significantly reduced pressor responses to intracerebro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…25,26 The AV3V area seems to function differently in SHR. As shown by Brody and colleagues, 25,27,28 lesions placed in this region interfered with several different forms of hypertension in rats 27,28 (DOCA-salt, Goldblatt, and Dahl salt-sensitive rats) but, by contrast, failed to affect the development or maintenance of hypertension in SHR. In SHR, the lesion of the AV3V region caused adipsia and the loss of pressor and dipsogenic responses to centrally administered angiotensin II, similar to what is observed in other rat strains.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…25,26 The AV3V area seems to function differently in SHR. As shown by Brody and colleagues, 25,27,28 lesions placed in this region interfered with several different forms of hypertension in rats 27,28 (DOCA-salt, Goldblatt, and Dahl salt-sensitive rats) but, by contrast, failed to affect the development or maintenance of hypertension in SHR. In SHR, the lesion of the AV3V region caused adipsia and the loss of pressor and dipsogenic responses to centrally administered angiotensin II, similar to what is observed in other rat strains.…”
Section: Discussionmentioning
confidence: 82%
“…However, electrical stimulation of the AV3V region in intact SHR caused smaller vasoconstrictor and vasodilator responses than observed in WKY, with a much smaller pressor response in SHR than in WKY. 27,28 Brody et al 28 suggested that the interrupted reflex arc that originates with renal afferent activation may be the base of the prevention of different forms of hypertension by the AV3V lesion. We postulate that the observed absence of response to central MR blockade in SHR depends on a dysfunction of the AV3V region.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining has provided biochemical evidence that NOS in the PVN is downregulated in the spontaneously hypertensive rat (SHR), a chronic heart failure rat model, a diabetic rat model, and a diet-induced obesity rat model (1,11,30,34,39,45,48,49,51). In addition, in two chronic models of hypertensive rats, central mineralocorticoid-induced hypertension and chronic renal failure, a significant decrease in the amount of nNOS mRNA was found in the hypothalamus and rostral and caudal ventrolateral medulla (39,45).…”
Section: Discussionmentioning
confidence: 99%
“…ROS production is increased in human and experimental hypertension and, moreover, plays an important role in blood pressure regulation (3,18,23,38). In the brain, ROS are recognized for their involvement in neurodegenerative diseases, but they have recently been implicated in modulating blood pressure and sympathetic nerve activity (4,10,11,35,47,50). In addition, recent observations in cardiac myocytes have demonstrated a unique interaction between NOS and superoxide such that a deficiency of nNOS leads to a profound increase in xanthine oxidoreductase-mediated superoxide production (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although lesion of the AV3V region attenuates blood pressure in many forms of experimental hypertension, 22 destruction of this area appears not to alter the course of hypertension in SHR. 34 Thus, if the AV3V tissue is not necessary for the expression of hypertension in SHR, then it follows that the increased angiotensinogen gene expression found in this area is not a necessary prerequisite for the hypertensive phenotype. Of course this does not mean that brain areas that lie outside of the AV3V region and express elevated angiotensinogen mRNA are unrelated to the hypertensive phenotype in SHR.…”
Section: Discussionmentioning
confidence: 99%